2002
DOI: 10.1051/0004-6361:20020253
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and magnetic wave heating in stars

Abstract: Abstract. Theoretical chromospheric models described in the two previous papers of this series are used to study the relationship between the chromospheric emission and the filling factor. This theoretically determined relationship shows that the chromospheric emission flux in Ca II (H+K) is approximately proportional to the square root of the magnetic filling factor at the stellar surface. To relate the filling factor to stellar rotation rate, we compare the theoretical fluxes with observations of stars with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…A similar agreement is also found with the results presented by Hempelmann (1995) who found f mag ∝ R −0.65±0.14 0 (2) the power law coefficient found by us (averaged over all spectral types) being b = −0.72 ± 0.13. Also in a more recent study on the chromospheric emission-magnetic filling factor relation, Fawzy et al (2002) found that an exponential law best fits the dependence of the theoretical filling factor on the rotational period, at least in the rotation range they analysed (10 ≤ P ≤ 40 d). We refer the reader to Paper I for a detailed discussion about the existence of the break at P ∼ 1.1 d in the A max -P and A max -R 0 relations and about differences with respect to previous studies.…”
Section: Activity-rotation Relationmentioning
confidence: 74%
“…A similar agreement is also found with the results presented by Hempelmann (1995) who found f mag ∝ R −0.65±0.14 0 (2) the power law coefficient found by us (averaged over all spectral types) being b = −0.72 ± 0.13. Also in a more recent study on the chromospheric emission-magnetic filling factor relation, Fawzy et al (2002) found that an exponential law best fits the dependence of the theoretical filling factor on the rotational period, at least in the rotation range they analysed (10 ≤ P ≤ 40 d). We refer the reader to Paper I for a detailed discussion about the existence of the break at P ∼ 1.1 d in the A max -P and A max -R 0 relations and about differences with respect to previous studies.…”
Section: Activity-rotation Relationmentioning
confidence: 74%
“…This paragraph really was written by VT). Chromospheres have to be heated, and it seems to take three sorts of input, acoustic waves, magnetic waves associated with flux tubes, plus magnetic reconnection (Fawzy et al 2002a(Fawzy et al , 2002b(Fawzy et al , 2002c.…”
Section: Stellar Activitymentioning
confidence: 99%
“…The analytical methods described above were used to compute the acoustic and magnetic (longitudinal + transverse + torsional) for stars with log g = 4 and different Teff (see Noble et al 2003a). The radiative losses were taken from Fawzy et al (2002c). The comparison clearly shows that there is a significant excess of the wave energy available for the acoustic heating (the acoustic fluxes should be compared only to the lower bound of the radiative losses) as well as for the magnetic heating (the magnetic fluxes should be higher than, or comparable to, the upper bound of the radiative losses) for stars with Teff ranging from 4000 K to 9000 K. Now, it remains to be determined whether these fluxes are sufficient to heat stellar chromospheres and transition regions.…”
Section: Wave Energy Available Versus Radiative Lossesmentioning
confidence: 99%